(untitled) (Journal of history, 2017)
The article discusses the impact factor of the Irish national liberation uprising on the relationship of Charles I and the Long Parliament during the English Revolution 1640-1660 years The history of relations between Britain and Ireland I half of XVII century, is one of the most important periods. The revolution that began in 1640 in England had a strong influence on neighboring countries and on the very first England. In the course of the revolution affected many internal and external factors, one of them is the Irish uprising began in 1641. Rise of nature was the national liberation and was directed against the long-term domination of the British colonialists. Charles I wanted to use the Irish rebels against the opposition Parliament, because I thought that the rebellion in Ireland is mainly directed against the Parliament, but not against the monarchy.